Applied technical analysis for advanced learners and practitioners : in charts we trust - Ramlall, Indranarain (Emerald Group Publishing Limited, 2016)
Technical analysis points out that the best source of information to beat the market is the price itself. Introducing readers to technical analysis in a more succinct and practical way, Ramlall focuses on the key aspects, benefits, drawbacks, and the main tools of technical analysis. Chart Patterns, Point & Figure, Stochastics, Sentiment indicators, Elliot Wave Theory, RSI, R, Candlesticks and more are covered, including both the concepts and the practical applications. Also including programming technical analysis tools, this book is a valuable tool for both researchers and practitioners.
Includes bibliographical references and index.
Print version record
Keywords: Econometrics; Business & Economics -- Econometrics; Econometrics